1993
DOI: 10.1161/01.hyp.22.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of norepinephrine-induced contractions by endothelin-1 in the rabbit aorta.

Abstract: Subthreshold concentrations of endothelin-1 potentiated the norepinephrine-induced contraction in isometrically mounted rings of the rabbit aorta. Pretreatment with endothelin-1 (0.1 nM) for 10 minutes increased the sensitivity of the aortic rings to norepinephrine without affecting the maximal contraction. This amplification was unaffected by removal of the endothelium but was prevented by the protein kinase C inhibitors staurosporine (0.01 (iM) and calphostin C (0.1 fiM). Pretreatment of the aortic rings for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
27
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 31 publications
9
27
0
Order By: Relevance
“…This is in agreement with previous studies that have demonstrated the occurrence of the phenomenon in vitro [15][16][17][18]22,23 or in vivo, 14,19 -21 as well as in humans. 14,20 -23 We have previously shown that this potentiation involves a sensitization of the contractile apparatus to calcium through the activation of protein kinase C. 15,17 Furthermore, we and others have also previously reported that endogenous endothelin-1 25 and angiotensin II 19 -21 take part in the control of vascular tone in resistance arteries and that the concentrations of hormones used in the present study are compatible with endogenous concentrations. Hence, role of endothelin-1 in the control of vascular tone can be altered, considering that vascular levels of endothelin-1 are modified in pathological situations such as hypertension.…”
Section: Iglarz Et Al Preproendothelin-1 Gene and Vascular Tonediscussupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previous studies that have demonstrated the occurrence of the phenomenon in vitro [15][16][17][18]22,23 or in vivo, 14,19 -21 as well as in humans. 14,20 -23 We have previously shown that this potentiation involves a sensitization of the contractile apparatus to calcium through the activation of protein kinase C. 15,17 Furthermore, we and others have also previously reported that endogenous endothelin-1 25 and angiotensin II 19 -21 take part in the control of vascular tone in resistance arteries and that the concentrations of hormones used in the present study are compatible with endogenous concentrations. Hence, role of endothelin-1 in the control of vascular tone can be altered, considering that vascular levels of endothelin-1 are modified in pathological situations such as hypertension.…”
Section: Iglarz Et Al Preproendothelin-1 Gene and Vascular Tonediscussupporting
confidence: 93%
“…Indeed, concentrations of endothelin-1 in the picomolar range are able to amplify the adrenergic-dependent tone through a reversible mechanism that does not change the amount of calcium required for the contraction. 15 In addition, as high K ϩ -induced contractions were similar in both groups, an alteration in the contractile apparatus should be excluded. We also found that both endothelium-dependent and -independent relaxations were unaffected by the mutation.…”
Section: Iglarz Et Al Preproendothelin-1 Gene and Vascular Tonediscusmentioning
confidence: 98%
See 1 more Smart Citation
“…In the rat mesenteric bed, ET-1 negatively modulates the release of NPY, but not NE (Hoang et al, 2002). Postjunctionally, ETs modulate sympathetic neurotransmission by enhancement of the contractile effect of both nerve stimulation and a variety of vasoactive agents (Henrion and Laher, 1993;Hoang et al, 2003). ET-1, through activation of the ET A receptor, potentiates the postjunctional contractile effects of ATP (Mutafova-Yambolieva and Radomirov, 1993;Hoang et al, 2003).…”
Section: Carbonyl]-4-methyl-l-leucyl]-1-(methoxycarbonyl)-d-tryptophymentioning
confidence: 99%
“…Briefly, second order renal arteries were dissected, and segment rings (2 mm) were prepared and mounted on nylon filaments in a myograph for resistance arteries (24). Segments of thoracic aorta (3 mm) were dissected and mounted on stainless steel wires in a classic myograph (25). Isometric tension was recorded using a force displacement transducer (MP 100; BioPac Systems, Inc., La Jolla, CA).…”
Section: Vascular Responses To Chemical Stimuli Renal Resistance Artmentioning
confidence: 99%